Calçando os tamancos de Paul-Michel: um estudo sobre a psicologia na problematização filosófica de Michel Foucault com base nos manuscritos inéditos dos anos 1950 - Francisco, Alessandro de Lima (2017)
This research refers mainly to Jacques Lagrange’s unpublished manuscripts related to courses offered by Michel Foucault at École Normale Supérieure de Paris, and deposited at Institut Mémoires de l’Édition Contemporaine. It also refers to those by Michel Foucault himself recently deposited at Bibliothèque Nationale de France. The latter focus on files concerning the 1950s –a period not to be ignored if one intends to understand the development of his researches, in order to apprehend the role of Psychology in Michel Foucault’s philosophical problematic. This research intends to show that – leaving from a discourse on psykhé (Psychology) and reaching a conduction of psykhé (Psykhogogía) - , Foucault’s considerations adopt an anti-psychologic posture, while they allow a new understanding of subjectivity